2023
DOI: 10.1186/s12887-023-03865-x
|View full text |Cite
|
Sign up to set email alerts
|

Iranian school-aged twin registry: preliminary reports and project progress

Abstract: Background National Persian school-aged twin registry was established to provide a platform for twin studies. In this report, we describe defining registry characteristics, database design, and preliminary results regarding gathered data in the first phase of the registry program. Method Through focus group discussions, the required data elements to design the database and data collection process were defined. First, a list of twins in school-aged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…In addition, school health experts (school nurses) play a crucial role as recruitment facilitators in school-aged twins. According to a previous study, there are approximately 189 738 twin students in Iran and 5642 twin students in Tehran 27. Similar studies have shown that schools can help children and adolescents develop healthy habits that will also benefit their families, friends and communities.…”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…In addition, school health experts (school nurses) play a crucial role as recruitment facilitators in school-aged twins. According to a previous study, there are approximately 189 738 twin students in Iran and 5642 twin students in Tehran 27. Similar studies have shown that schools can help children and adolescents develop healthy habits that will also benefit their families, friends and communities.…”
Section: Resultsmentioning
confidence: 89%
“…By promoting their health, schools can enhance the quality of life of children and teenagers. School staff, such as school health experts (school nurses), could serve as recruitment facilitators to improve participant retention 27 44. Therefore, school-aged twins are considered a desirable group of twins in registries.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations